2017
DOI: 10.1007/s11262-017-1465-8
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the us7 and us8 genes of pseudorabies virus exerts a differential effect on the expression of early and late viral genes

Abstract: The pseudorabies virus (PRV; also known as Suid herpesvirus-1) is a neurotropic herpesvirus of swine. The us7 and us8 genes of this virus encode the glycoprotein I and E membrane proteins that form a heterodimer that is known to control cell-to-cell spread in tissue culture and in animals. In this study, we investigated the effect of the deletion of the PRV us7 and us8 genes on the genome-wide transcription and DNA replication using a multi-time-point quantitative reverse transcriptase-based real-time PCR tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The literature of the gE/gI protein complex is focused around the function of the protein in cellular sorting, viral spreading and related, or the use of gE/gI mutant viruses as vaccine (due to its attenuation). Thus, our recently published work (Póka et al 2017) with results that were shown in this thesis along with others that are not detailed here, sheds light to a new area of PRV research.…”
Section: Discussionsupporting
confidence: 70%
“…The literature of the gE/gI protein complex is focused around the function of the protein in cellular sorting, viral spreading and related, or the use of gE/gI mutant viruses as vaccine (due to its attenuation). Thus, our recently published work (Póka et al 2017) with results that were shown in this thesis along with others that are not detailed here, sheds light to a new area of PRV research.…”
Section: Discussionsupporting
confidence: 70%
“…With the above results, the reduced expression of the UL11 could affect the viral replication. The ICP22 ( Fraser and Rice, 2007 ; Li et al, 2020 ), ICP27 ( Tang et al, 2019 ), and ICP4 ( Frasson et al, 2021 ) are immediate early genes, and UL11 ( Yang et al, 2021 ), UL16 ( Oshima et al, 1998 ; He et al, 2012 ), UL21 ( Yang et al, 2020 ), gE ( Po’ka et al, 2017 ) and gB ( Ramachandran et al, 2010 ) are late genes, and the US3 ( Labiuk et al, 2010 ) is an early gene. Nevertheless, how DPV UL11 takes part in the viral replication process, we still do not know.…”
Section: Resultsmentioning
confidence: 99%
“…Herpesviruses consist of four morphologically differentiable structures: a nucleoprotein core containing genomic DNA, an icosahedral capsid consisting of 162 capsomers, a proteinaceous layer of electron-dense material (tegument) augmenting the capsid, and a viral envelope as the outermost layer(6). In addition, all herpesviruses conform to the same structural plan (7). It is well known that the assembled nucleocapsid of herpesviruses in the nucleus acquires the primary envelope by budding from the inner nuclear membrane and loses it by fusing with the outer nuclear membrane to cross the nuclear membrane(8).…”
Section: Introductionmentioning
confidence: 99%